1991
DOI: 10.1016/0014-5793(91)80597-v
|View full text |Cite
|
Sign up to set email alerts
|

Localization of metallothionein in nuclei of growing primary cultured adult rat hepatocytes

Abstract: 1, INTRODUCTION MetallotlCxxins(MTs), low molecular-weight, heavy-metal-binding, cysteinc-rich cyrosolic proteins were first isolated from horse kidney and characterized by Vallee and co-workers [1,2]. Since then, MTs have been found in a number of species [3]. The function of MT has been debated ever since its discovery. A role in metal metabolism or detoxification is strongly suggested by the ability of MTs to bind to and be induced by heavy metal ions [4], Kelley et al, reported that overexpression of MT re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
0
2

Year Published

1993
1993
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(65 citation statements)
references
References 10 publications
1
62
0
2
Order By: Relevance
“…In cultured adult rat hepatocytes, metallothionein accumulates in nuclei at early S-phase, but not at Go or G1 when the protein is extranuclear (Tsujikawa et al, 1991). Modulation of animal thionein biosynthesis, or intracellular distribution (nuclear or extranuclear), could affect DNA binding by Zn2+-requiring transcription factors and thereby regulate the activity of a large subset of genes (Zeng et al, 1991a,b).…”
Section: Metallothioneins In Other Kingdomsmentioning
confidence: 99%
“…In cultured adult rat hepatocytes, metallothionein accumulates in nuclei at early S-phase, but not at Go or G1 when the protein is extranuclear (Tsujikawa et al, 1991). Modulation of animal thionein biosynthesis, or intracellular distribution (nuclear or extranuclear), could affect DNA binding by Zn2+-requiring transcription factors and thereby regulate the activity of a large subset of genes (Zeng et al, 1991a,b).…”
Section: Metallothioneins In Other Kingdomsmentioning
confidence: 99%
“…For example, it was demonstrated that MT is localized mainly in the nucleus during development (23,24). It can be argued that, because MT is localized mainly in the nucleus during development, its limited availability to the degradation machinery (cytosol and/or lysosomes) might be a factor that can regulate its accumulation in the cell during development.…”
Section: Conclusion and Future Prospectsmentioning
confidence: 99%
“…and in mechanisms controlling growth, differentiation and proliferation of cells, explicating their nuclear vs. cytoplasmic localization (Dziegiel, 2004). MTs are not only cytoplasmic protein, but also accumulate in lysosomes, yet could be transported to the nucleus and to the intermembrane space of mitochondria (Tsujikawa et al, 1991;Ye et al, 2001). Notably, they are also not merely intracellular, and could be exported from cells and absorbed by other cells via a receptor-mediated mechanism, in which the protein remains in an endocytotic compartment and the metal could be transported to the cytosol (Moltedo et al, 2000;Wolff et al, 2006;Hao et al, 2007).…”
Section: Introductionmentioning
confidence: 99%